PENGARUH MASSAGE EFFLEURAGE TERHADAP PENURUNAN NYERI DISMENORE PRIMER PADA REMAJA PUTRI DI SMA N 1 SUTERA KABUPATEN PESISIR SELATAN - Zuraida Zuraida; Missi Aslim (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Dysmennorrhea is mentrual pain which comes in cramps and centered in the lower part of stomach during menstruation, even it happens severely that it distrubs activities. The purpose of this research is to determine the effect of effleurage massage in decreasing menstrual pain in teenagers in SMA N 1Sutera Kabupaten Pesisir Selatan. The type of this research was quantitative-quasy experimental design with the one group pretest-posttest approach. Purposive sampling was used to get the samples. Then, 15 students were chosen as the samples. The research was conducted in SMAN 1 Sutera Kabupaten Pesisir Selatan on August to September 2018. Then, it was tested by a statistical test T-test with a confidence degree of 95% or p